Wave forces and dynamic pressures on pile-supported breakwaters with inclined perforated plates under regular waves - Li, Ziwang; Liu, Rui; Wang, Zhenlu; Liang, Bingchen; Xia, Haofeng; Sun, Xuehai; Wang, Xinpeng; Shi, Luming (Frontiers in Marine Science, 2024)
The use of pile-supported breakwaters can be a cost-effective solution for wave energy dissipation when traditional rubble mound breakwaters are not suitable. For a cost-effective design of these barriers, it is essential to obtain accurate estimates of dynamic pressures and wave forces. Laboratory experiments were conducted to investigate the dynamic pressures and forces on a novel pile-supported breakwater with inclined perforated plates. The analysis focused on various wave and structural parameters, including incident wave height, wave period, plate porosity, and plate configuration. For double-layer configurations with the same porosity, dynamic pressures on the single-layer or front plate were significantly higher than on the rear plate, with rear plate forces being 20% to 60% less. The dynamic pressure on the rear plate exhibited a uniform vertical distribution. Varying plate porosity at different locations significantly impacted structural forces. Gradually decreasing porosity improved wave dissipation and reduced forces on the plates, with front and back plate forces reaching approximately 70% of those on single-layer plates. Optimal protection across various wave periods can be achieved by adjusting porosity and plate arrangement. These findings provide valuable insights for designing pile-supported breakwaters in coastal protection engineering.